Routine treatment pathways in a cohort of patients with major depression and suicidality in Italy: the ARIANNA observational study - Maurizio Pompili; Bernardo Maria Dell'Osso; Gianluca Rosso; Mario Amore; Antonello Bellomo; Antonio Mautone; Elisa Pilotto; Sandra Ramacciotti; Maria Ilaria Scardigli; Giuseppe Ascione; Riccardo Cipelli; Carmen Sansone; et al. (Comprehensive Psychiatry, 2023)
Background: Major Depressive Disorder (MDD) with suicidal ideation, intent, or behavior is a psychiatric emergency with controversial care management. Our study describes the comprehensive treatment pathways of this population in Italian routine clinical practice. Methods: ARIANNA [NCT 04463108] is an observational prospective and retrospective cohort study involving both primary data collection and secondary data extract. A total of 137 adult MDD patients with suicidality were enrolled from 24 Italian care sites and followed for 90 days. Other than the description of treatment patterns, the impact of treatment on depressive symptoms and suicidality, the burden on the patient's and caregiver's quality of life, healthcare resource utilization and costs were described. Results: Of the 133 eligible patients, 68.4% were female, and the median age was 47. Approximately half of the study population had a current severe major depressive episode. Treatment strategies at the time of active suicidal ideation with intent definition/confirmation (t0) were heterogeneous, increasing in complexity during observation. According to the MADRS, patients with remission at t0+1 day were 2.6%, with the mean total score decreasing from 37.2 at t0 to 32.3. Limitations: The study sites were not randomly selected. Conclusions: To the best of our knowledge, this is the first cohort study that prospectively describes the characteristics of patients with MDD and suicide risk in Italy, and how they are treated in clinical practice. The study confirms this is a difficult-to-treat population. In addition, a lack of rapid, effective treatment for reducing depressive symptoms and suicidality is observed.